Progesterone reduces depression-like behavior in a murine model of Alzheimer’s Disease - Frye, Cheryl A. (Springer Netherlands, 2009)
Although anxiety and depression are not the core symptoms of Alzheimer’s Disease (AD), there are changes observed in mood in those with AD, as well as in the aging population. Anxiety and depression may be influenced by progesterone P(4) and/or its neuroactive metabolites, dihydroprogesterone (DHP) and 5α-pregnan-3α-ol-20-one (3α,5α-THP). To begin to investigate progestogens’ role in AD, a double transgenic mouse model of early-onset familial AD that co-overexpresses mutant forms of amyloid precursor protein (APPswe) and presenilin 1 Δ exon 9 mutation was utilized. As such, the effects of long-term (from 6 to 12 months of age) administration of P(4) to ovariectomized (ovx) wildtype and APPswe+PSEN1Δe9 mice for changes in affective behavior was investigated. APPswe+PSEN1Δ9 mutant mice had increased anxiety-like (i.e., increased emergence latencies, decreased time spent on the open quadrants of the elevated zero maze) and increased depressive-like behavior (i.e., increased time spent immobile) than did wildtype mice. Compared to vehicle-administration, P(4) administration (which produced physiological circulating P(4), DHP, and 3α,5α-THP levels, particularly in the wildtype mice) decreased depressant-like behavior in the forced swim test. These effects occurred independent of changes in general motor behavior/coordination, pain threshold, and plasma corticosterone levels. Thus, the APPswe+PSEN1Δ9 mutation alters affective behavior, and P(4) treatment reversed depressive-like behavior.